Strength and stiffness of new designed externally invisible and demountable joints for furniture cases. (15th November 2019) - Krzyżaniak, Łukasz; Smardzewski, Jerzy
Graphical abstract: Highlights: New original externally invisible furniture joints core were designed. Joints are manufactured from cheap and eco-friendly materials. Prototype joints are an attractive alternative to replace standard eccentric joints. Shapes of joints are guaranteeing high strength and stiffness. Abstract: The distribution of furniture sold in the form of flat packages requires the use of appropriate joints. Such joints should be functional, esthetically attractive, durable and safe to use. It was decided in this study to manufacture prototypes of innovative furniture joints and evaluate their quality compared to the most popular eccentric joints. The aim of these analyses was to determine the effect of assembly forces on stiffness and strength of designed furniture joints. The study presents the method applied to determine assembly forces in selected joints and specifies the method used to determine stiffness and strength of joints. This work also presents numerical models of joints selected for analyses and experimental results concerning strength and stiffness of joints as well as their dependence on assembly forces. The results of numerical calculations of stresses caused by load were compared with the results of experimental measurements. Based on the analysis of recorded results it was shown that assembly forces have the greatest effect on joint strength. An advantageous design of the slide catch joint provides a uniform distribution of assembly stresses compared to concentrated stresses generated in an eccentric joint.